3N

Tìm x biết: 9x2 + 6x + 4y2 - 8y + 5 = 0

NL
31 tháng 10 2020 lúc 19:58

Phương trình tương đương (3x)2+2.3x+1+(2y)2−2.2x.2+4=0(3x)2+2.3x+1+(2y)2−2.2x.2+4=0 ⇒(3x+1)2+(2y−2)2=0⇒(3x+1)2+(2y−2)2=0 Do (3x+1)2≥0(3x+1)2≥0 và (2y−2)2≥0(2y−2)2≥0 ∀x,y∀x,y ⇒(3x+1)2+(2y−2)2≥0⇒(3x+1)2+(2y−2)2≥0 Dấu "=" xảy ra ⇔⇔ ⇒{(3x+1)2=0(2y−2)2=0⇒{(3x+1)2=0(2y−2)2=0 ⇒{3x+1=02y−2=0⇒{3x+1=02y−2=0 ⇒⎧⎨⎩x=−13y=1



hok tốt

Bình luận (0)
 Khách vãng lai đã xóa
IA
31 tháng 10 2020 lúc 19:59

\(9x^2+6x+4y^2-8y+5=0\)

\(\Leftrightarrow9x^2+6x+1+4\left(y^2-2y+1\right)=0\)

\(\Leftrightarrow\left(3x+1\right)^2+4\left(y-1\right)^2=0\)

\(\Leftrightarrow\hept{\begin{cases}3x+1=0\\y-1=0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=-\frac{1}{3}\\y=1\end{cases}}\)

vậy.......

Bình luận (0)
 Khách vãng lai đã xóa
NN
31 tháng 10 2020 lúc 20:00

\(9x^2+6x+4y^2-8y+5=0\)

\(\Leftrightarrow\left(9x^2+6x+1\right)+\left(4y^2-8y+4\right)=0\)

\(\Leftrightarrow\left(3x+1\right)^2+4\left(y^2-2y+1\right)=0\)

\(\Leftrightarrow\left(3x+1\right)^2+4\left(y-1\right)^2=0\)(1)

Vì \(\left(3x+1\right)^2\ge0\forall x\)\(4\left(y-1\right)^2\ge0\forall y\)

\(\Rightarrow\left(3x+1\right)^2+4\left(y-1\right)^2\ge0\forall x,y\)(2)

Từ (1) và (2) \(\Rightarrow\left(3x+1\right)^2+4\left(y-1\right)^2=0\)

\(\Leftrightarrow\hept{\begin{cases}3x+1=0\\y-1=0\end{cases}}\Leftrightarrow\hept{\begin{cases}3x=-1\\y=1\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-\frac{1}{3}\\y=1\end{cases}}\)

Vậy \(x=-\frac{1}{3}\)\(y=1\)

Bình luận (1)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
NA
Xem chi tiết
TT
Xem chi tiết
PB
Xem chi tiết
DH
Xem chi tiết
HV
Xem chi tiết
GV
Xem chi tiết
H24
Xem chi tiết
NA
Xem chi tiết
H24
Xem chi tiết